2004
DOI: 10.1001/archsurg.139.9.961
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Surgical Treatment of Advanced-Stage Melanoma

Abstract: The clinical treatment of patients with stage IV melanoma according to criteria of the American Joint Committee on Cancer (AJCC) is controversial because the 5-year survival rate is approximately 5%. Specific clinicopathologic factors are predictive of survival following curative surgery. Design: Cohort analysis of 1574 successive patients undergoing surgical resection of metastatic melanoma for a 29-year period. Patients received follow-up on a routine basis with serial examinations and radiographic studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
128
1
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(140 citation statements)
references
References 38 publications
2
128
1
6
Order By: Relevance
“…Hepatic resection offers the possibility of long-term survival in patients with liver-limited metastasis (14). In patients with unresectable melanoma, empirical systemic chemotherapy is the best treatment option, if their performance status is adequate.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic resection offers the possibility of long-term survival in patients with liver-limited metastasis (14). In patients with unresectable melanoma, empirical systemic chemotherapy is the best treatment option, if their performance status is adequate.…”
Section: Discussionmentioning
confidence: 99%
“…Cloquet lenf nodu biyopsisi mikroskopik hastalık varlığında, dördün altında lenf nodu tutulumunda veya klinik lenf nodu tutulumu olmadığında önerilmektedir. Chu ve arkadaşları, tamamlayıcı yüzeyel inguinal diseksiyon sonrası senkron pelvik hastalık görülme oranını %11,9 olarak (52). 1 yıllık sağkalım %50 civarındadır.…”
Section: Cerrahi Tekniklerunclassified
“…When complete resection is performed in the setting of distant disease, five-year survival rates in the range of 20-25%, and as high as 40%, may be achieved . Importantly, one study showed that, while patients who undergo complete resection of metastatic melanoma have a 5 year survival rate of 23%, the figure was 6% in patients who either do not undergo surgery or have gross residual disease remaining following surgery (R2 resection) [Agrawal et al, 1999;Essner et al, 2004;Ollila et al, 1996;Rose et al, 2001].…”
Section: Resection Of Distant Metastatic Diseasementioning
confidence: 99%
“…For example, patients with a disease-free interval of greater than 36 months at the time of recurrence and those with a solitary metastasis have better outcomes a [Essner, 2003;Essner et al, 2004]. Tumor doubling time has also been correlated with prognosis; a tumor doubling time of greater than 60 days is associated with a more favorable prognosis relative to a shorter doubling time [Ollila et al, 1998].…”
Section: Wwwintechopencommentioning
confidence: 99%